Antioxidant nutrients in plasma of Japanese patients with chronic obstructive pulmonary disease, asthma‐COPD overlap syndrome and bronchial asthma - Kodama, Yuzo; Kishimoto, Yuki; Muramatsu, Yoko; Tatebe, Junko; Yamamoto, Yu; Hirota, Nao; Itoigawa, Yukinari; Atsuta, Ryo; Koike, Kengo; Sato, Tadashi; Aizawa, Koich; Takahashi, Kazuhisa; et al. (The clinical respiratory journal, 2017)
Background Few studies to date have investigated the antioxidant nutrients such as vitamin C (ascorbic acid), vitamin E (α‐tocopherol), retinol and carotenoids in plasma from patients with pulmonary disease in Japan. To clarify the role of antioxidant nutrients such as vitamin C, vitamin E, retinol and various carotenoids in plasma of Japanese patients with chronic obstructive lung diseases (COPD), asthma‐COPD overlap syndrome (ACOS) and/or bronchial asthma (BA), we compared to healthy elderly controls. Methods Ascorbic acid (AA), carotenoids (lutein, zeaxanthin, β‐cryptoxanthin, α‐carotene, β‐carotene and lycopene), retinol and α‐tocopherol levels in plasma were determined by using a high performance liquid chromatography. Reduced glutathione (GSH), oxidised glutathione (GSSG) in whole blood and urinary 8‐OHdG were also determined. Results Plasma AA level of COPD subjects was significantly lower than that of healthy elderly people. Conversely, ACOS and BA subjects showed no significant difference from healthy elderly people. Moreover, plasma lycopene and total carotenoid levels and GSH content in blood were significantly lower in COPD subjects than these in healthy elderly people. However, other redox markers such as GSSG, GSH/GSSG ratio and urinary 8‐OHdG found no significant differences between COPD, ACOS and BA compared to healthy elderly people. Conclusions These results suggested that COPD of Japanese patients may develop partly because of oxidative stress derived from a shortage of antioxidant nutrients, especially of AA and lycopene, as well as GSH while this may not be the case in both ACOS and BA.